MENGEMBANGKAN DAN MENGUATKAN MINAT ENTERPRENEURSHIP PADA REMAJA DIERA KEBIASAAN BARU - Tri Sugiarti Ramadhan; Rizkita Oktavirana (Jurnal Abdi Insani, 2022)
The pandemic condition opens up opportunities for teenagers to do business. Online learning makes teenagers who go to school or college have a lot of free time, especially teenagers who are very close to gadgets which are an effective medium for marketing during the current pandemic. In this condition, it is expected that teenagers can use their time positively and productively. Mental readiness and skills need to be prepared before someone enters the business world. Based on this, the objectives of entrepreneurship development for teenagers are as follows: 1) the growth of an entrepreneurial spirit, 2) encouraging in exploring entrepreneurial potential through creative ideas, 3) being able to make a business plan, 4) being able to run a business supported by creative e-marketing . The methods used are lectures, independent assignments, presentations, discussions and business practices. Activities carried out include entrepreneurship training, business planning training, use of social media, business plan presentations and business practices. After the entrepreneurship development activities are carried out, an evaluation is carried out. The results show that 100% of participants stated that they experienced an increase in knowledge and skills after participating in the activity and 90% showed a change in attitude, namely running a business.